Pengembangan Flipbook Berbasis Think Pair Share Pada Materi Pertumbuhan dan Perkembangan Pada Tumbuhan - widya ningrum; Rahmi Astati Lemba Kamunggul; Nila Kartikasari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Learning basically involves teachers and students as components of the audience. Professional teachers should be able to develop teaching materials independently according to the needs of students. However, teachers at Baiturrohmah Islamic High School Malang have not done this. Teachers still use worksheets on the market. Teachers have not used media that are able to motivate students in learning. The solution to this problem as well as the aim of the research is to develop a flipbook based on the Think Pair Share (TPS) model on plant growth and development materials. The research method uses R&D with a 4D development model consisting of define, design, develop, and disseminate. The research instrument used a questionnaire. This research is limited to the develop stage. The results showed that the percentage was 87.5% (material expert assessment), 80% percentage (media expert assessment), 97.6 percentage (teacher assessment), 87.5 percentage (student readability test). Overall the product is ready to be used in learning